2023
DOI: 10.1186/s12866-023-02764-6
|View full text |Cite
|
Sign up to set email alerts
|

Is there a placental microbiota? A critical review and re-analysis of published placental microbiota datasets

Abstract: The existence of a placental microbiota is debated. The human placenta has historically been considered sterile and microbial colonization was associated with adverse pregnancy outcomes. Yet, recent DNA sequencing investigations reported a microbiota in typical human term placentas. However, this detected microbiota could represent background DNA or delivery-associated contamination. Using fifteen publicly available 16S rRNA gene datasets, existing data were uniformly re-analyzed with DADA2 to maximize compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 180 publications
1
17
0
Order By: Relevance
“…Historically, the placenta was considered a sterile organ, but, in recent years, new evidence has demonstrated the possible existence of a placental microbiome. In 2014, the first studies based on bacterial DNA demonstrated the existence of a placental microbiota even during full-term and normal pregnancies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the placenta was considered a sterile organ, but, in recent years, new evidence has demonstrated the possible existence of a placental microbiome. In 2014, the first studies based on bacterial DNA demonstrated the existence of a placental microbiota even during full-term and normal pregnancies [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lv et al observed an expansion in the relative abundance of periodontal disease-associated bacteria, such as Fusobacterium , and a decrease in the abundance of SCFA-producing bacteria, such as Faecalibacterium and Akkermansia , in the gut microbiome of women with early-onset PE [ 225 ]. There is ongoing debate regarding the existence and role of a placenta-specific microbiome [ 226 ].…”
Section: Mechanisms Of Action Of Nutritional Factors In the Pathophys...mentioning
confidence: 99%
“…However, this statement has recently been reassessed by a limited number of studies confirming the presence of microorganisms in the placenta [ 24 , 25 , 26 ]. These results are still the subject of debate in the scientific community, and there is no clear conclusion [ 27 ].…”
Section: The Mode Of Delivery and Microbiota Transfermentioning
confidence: 99%